Hedwig and the Angry Inch [videorecording (DVD)] - Mitchell, John Cameron; Mitchell, John Cameron; Mitchell, John Cameron; Pitt, Michael, 1981-; Shor, Miriam; Liscinski, Theodore; Trask, Stephen (Criterion collection, 2019)
Hedwig, transexual punk rock girl from East Berlin, comes to America with her band, determined to find fame, fortune, and love.